Ghana: Systematic analysis of world market and domestic production shocks - Mukashov, Askar; Pauw, Karl; Jones, Eleanor; Thurlow, James (International Food Policy Research Institute, 2025)
Achieving development goals is subject to economic uncertainties, yet policymaking rarely accounts for these risks. This Country Brief quantifies the risks facing Ghana’s economy and population, focusing on two primary sources: 1) External risks stemming from shocks in international commodity prices and foreign capital flows and 2) Domestic risks associated with production shocks in volatile sectors of the Ghanaian economy, such as primary agriculture and hydropower electricity generation, are often caused by extreme weather. The significance of these risks is assessed based on the range of the shocks’ impacts on four main economic and development indicators: total GDP, private consumption, poverty rate, and prevalence of undernourishment. The analysis uses data mining methods to simultaneously sample many shocks from historical data, con structing a comprehensive set of realistic shock scenarios for Ghana. A country-specific, economywide Computable General Equilibrium (CGE) model then simulates the impacts of these shocks on both total and sector-specific economic outcomes, deriving changes in poverty and undernourishment for each shock scenario. Finally, machine learning techniques are applied to obtain metrics for the relative im portance of different risk factors. The results suggest that Ghana’s trade-oriented economy is predominantly exposed to external risks, with fluctuations in world prices of key exports—particularly energy and metals—significantly influencing eco nomic activity and the country’s ability to finance imports. Poverty and undernourishment risks present a more complex picture, with a significant difference between urban and rural risk factors. Rural households, which are generally poorer than urban households and constitute the majority of the poor and undernourished population, are more exposed to domestic production volatility factors. Understanding these economic risks is a critical first step in facilitating discussions on potential risk management strategies, such as promoting domestic productivity growth and diversifying economic activity away from high-risk sectors.